2017
DOI: 10.1103/physreve.95.010203
|View full text |Cite
|
Sign up to set email alerts
|

Smallest chimera states

Abstract: We demonstrate that chimera behavior can be observed in small networks consisting of three identical oscillators, with mutual all-to-all coupling. Three different types of chimeras, characterized by the coexistence of two coherent oscillators and one incoherent oscillator (i.e. rotating with another frequency) have been identified, where the oscillators show periodic (two types) and chaotic (one type) behaviors. Typical bifurcations at the transitions from full synchronization to chimera states and between dif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
61
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(68 citation statements)
references
References 48 publications
6
61
0
Order By: Relevance
“…However, it has been shown for phase oscillator networks that time delay can also induce multi-chimeras 23 . The existence of chimera states in sys-tems with time-delayed couplings has been also reported in 50,[63][64][65][66] . In particular, for coupled phase oscillator systems it has been found that chimeras are robust to small time delays and delay distributions 64 and can become unstable depending on the value of delay 65 .…”
Section: Time-delayed Couplingmentioning
confidence: 89%
“…However, it has been shown for phase oscillator networks that time delay can also induce multi-chimeras 23 . The existence of chimera states in sys-tems with time-delayed couplings has been also reported in 50,[63][64][65][66] . In particular, for coupled phase oscillator systems it has been found that chimeras are robust to small time delays and delay distributions 64 and can become unstable depending on the value of delay 65 .…”
Section: Time-delayed Couplingmentioning
confidence: 89%
“…Different kinds of chaotic attractors with partially broken symmetry have been investigated there beyond phase oscillator systems. The authors of the article [25] have described regular and chaotic chimera states in the system of three coupled phase oscillators with inertia. These states have been detected in experiments with mechanical systems [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, examples of chimera regimes within rather small sets of oscillators have been reported 3 . Recent studies have revealed that chimera states can be quite complex.…”
Section: Introductionmentioning
confidence: 99%